Application of the edu finance model to improve financial literature in creative industry in Sidoarjo district - Eko Purwanto; Muhadjir Anwar (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
Purpose: This research aimed to observe the development of SMEs problems that related with financial knowledge. The importance of educating SMEs in a systematic, integrated and sustainable manner regarding financial literacy is expected to be able to build a strong business foundation which is very much needed. Increasing financial literacy is expected to contribute to financial system stability, reduce vulnerabilities in the financial system and make effective decisions on financial resources.Design/methodology/approach: The data were collected through self-administered questionnaire. There were 14 items used to edu finance and financial literature . The research design used in this research is quantitative research because it uses data in the form of numbers in descriptive statistical analysis. The results of these calculations will then be compared with the criteria for the level of financial literacy according to Chen and VolpeFindings: The results of this study indicate that based on the five variables that use the financial literacy level of SMEs, women are in the low category. Therefore, an appropriate model is needed to increase financial literacy knowledge in creative industry SMEs in Sidoarjo District, by prioritizing the importance of planning and evaluation that produces feedback for improving financial literacy.Research limitation/implications: The data were collected fromMSME creative industry sector in Sidoarjo District. It is limited in that it may not have captured the reflections of MSME creative industry sector in Indonesia that maybe differed from the sample used. Practical implications: The condition of SMEs in the creative industry sector in Sidoarjo District currently still has limitations with various problems. The limitations experienced include financial skills, and financial behavior, limited access to information and technology. Therefore, financial literacy is crucial for SMEs to improve their business performance. Several studies have been conducted to prove that financial literacy contributes to the improvement of MSME performanceOriginality/value: This research contributed to identifying how respondents need a Systematic, integrated, and sustainable education for SMEs regarding financial literacy is needed to build a strong business foundation.